Karakteristik Tekanan Darah dan Antropometri dari Responden dengan Hasil Elektrokardiogram Normal dan Suspect Coronary Artery Disease – Penelitian Survei Masyarakat (Single Center) - David Dwi Ariwibowo; William Gilbert Satyanagara; Dean Ascha Wijaya; Hendsun Hendsun; Nadela Nadela (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2023)
Coronary artery disease (CAD) is a significant cardiovascular disease that affects the human population worldwide. There are several risk factors that contribute to the development of this cardiovascular disease, including lifestyle, environmental factors, and genetic factors. This survey study aims to examine the characteristics of age, gender, blood pressure, body mass index, hip circumference, waist circumference, and arm circumference in the normal EKG group, EKG suspect coronary artery disease group, and the total research sample at SMA Kalam Kudus II Jakarta, selected based on total sampling criteria during the period of May - June 2023. The variables used in this study are age, gender, blood pressure, body mass index, hip circumference, waist circumference, arm circumference, and electrocardiogram (ECG) examination. All examinations were conducted according to standard procedures and protocols. Among the 52 respondents, the characteristics of the respondents in terms of gender, age, blood pressure, body mass index, hip circumference, waist circumference, and arm circumference were not significantly different among the normal EKG group, EKG suspect CAD group, and the total sample.